2001
DOI: 10.1093/hmg/10.14.1511
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of inducible HSP70 chaperone suppresses neuropathology and improves motor function in SCA1 mice

Abstract: Many neurodegenerative diseases are caused by gain-of-function mechanisms in which the disease-causing protein is altered, becomes toxic to the cell, and aggregates. Among these 'proteinopathies' are Alzheimer's and Parkinson's disease, prion disorders and polyglutamine diseases. Members of this latter group, also known as triplet repeat diseases, are caused by the expansion of unstable CAG repeats coding for glutamine within the respective proteins. Spinocerebellar ataxia type 1 (SCA1) is one such disease, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
222
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(236 citation statements)
references
References 24 publications
11
222
0
3
Order By: Relevance
“…Postmitotic neurons appear to be particularly sensitive to protein misfolding because aggregated toxic proteins cannot be diluted by cell division [51]. Malfunctioning of broadly expressed proteins involved in translation and protein folding manifests specifically neurotoxic effects in mouse [51,52] On the contrary, overexpression of chaperones has been reported to suppress neurodegeneration in fruit fly and mouse models [53,54]. Indeed, neurons were highlighted by Drummond and Wilke as being highly susceptible to translational infidelity and the fitness cost of misfolding [21].…”
Section: Mistranslation-induced Protein Misfolding Hypothesismentioning
confidence: 99%
“…Postmitotic neurons appear to be particularly sensitive to protein misfolding because aggregated toxic proteins cannot be diluted by cell division [51]. Malfunctioning of broadly expressed proteins involved in translation and protein folding manifests specifically neurotoxic effects in mouse [51,52] On the contrary, overexpression of chaperones has been reported to suppress neurodegeneration in fruit fly and mouse models [53,54]. Indeed, neurons were highlighted by Drummond and Wilke as being highly susceptible to translational infidelity and the fitness cost of misfolding [21].…”
Section: Mistranslation-induced Protein Misfolding Hypothesismentioning
confidence: 99%
“…One can envision that transfer of nonfoldable substrates to HSP70 would result in a fatuous ATP‐driven substrate binding and release, which may slightly delay aggregation but not prevent it. Indeed, in cells overexpression of HSP70s only marginally affects polyQ aggregation (Chai et al ., 1999; Rujano et al ., 2007), whereas in vivo HSP70‐mediated rescue of polyQ toxicity only occurs in the presence of semi‐soluble nuclear polyQ aggregates (Warrick et al ., 1999; Chan et al ., 2000; Cummings et al ., 2001). Thus, the different small HSPs with different affinities to substrates and HSP70s may have evolved to serve adequate processing of a broad spectrum of clients.…”
Section: Discussionmentioning
confidence: 99%
“…To define the role of different protein domains in the onset and progression of the disease, models that differ in either the length of the polyQ tract inserted (Lorenzetti et al, 2000) or the specific mutation induced (Klement et al, 1998) have been generated. To investigate the cellular pathways that influence disease progression, SCA1 transgenic mice have been crossed with either transgenic mice or mice that are deficient in genes involved specifically in protein degradation or stress responses (Cummings et al, 1999;Shahbazian et al, 2001;Cummings et al, 2001;Okuda et al, 2003). Recently, it has been demonstrated that blocking the expression of mutant ATAXIN1 in a conditional mouse model of SCA1 modifies the progression of the disease (Zu et al, 2004;Serra et al, 2006).…”
Section: Introductionmentioning
confidence: 99%